Brain Injury Patterns after Neonatal Hypoglycemia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Brain injury patterns on early MRI and neurodevelopmental outcome after symptomatic neonatal hypoglycemia were studied in 35 term infants at Hammersmith Hospital, Imperial College London, UK.